x^2+17x+42

x^2 +17x+42

you look for two factors when you multiply you get 42x^2 and their sum is17x

which are not possible

then the expression remains x^2+17x+42

x^2+17x/2+(17/2)^2=-42+(17/2)^2

x^2+(17/2)^2=-42+289/4

(x+17/2)^2=30.25

square root from both sides

x+17/2=+-5.5

x=-8.5+-5.5

x=-8.5+5.5

x=-3 or x=-14

(x+3)(x+14)

x^2+14x+3x+42

x(x+14)+3(x+14)

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up